Computational Methods and Experimental Testing In Mechanical Engineering Selected Papers from the 6th Algerian Congress on Mechanics, CAM 2017, November 26-30, 2017, Constantine, Algeria - Boukharouba, Taoufik; Chaari, Fakher; Ben Amar, Mounir; Azouaoui, Krimo; Ouali, Nourdine; Haddar, Mohamed; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers a variety of topics in mechanics, with a special emphasis to fluid mechanics and energy transfer. Chapters are based on selected contributions presented during the Algerian Congress of Mechanics (CAM 2017), held on November 26 - 30, 2017, in Constantine, Algeria. The book covers theoretical analysis, modeling, and numerical treatment of performance-related problems of new refrigeration systems, heating and cooling. It reports on experimental research to solve problems related to the flow of microfluids, and relevant applications in the areas of chemical engineering, biochemistry, biomedicine and renewable energy. Further topics include methods for maintenance of mechanical structures, strength, wear, fracture, damage and life of structures, and image processing solutions for the design and 3D manufacturing of mechanical parts. Improvement, control and regulation of urban road traffic are also discussed in this book, thus offering a comprehensive, practice-oriented reference guide for academics and professionals.
Keywords: Mechanics, Applied; Solids; Manufactures; Multibody systems; Vibration; Solid Mechanics; Machines, Tools, Processes; Multibody Systems and Mechanical Vibrations